Wearing the niqab and blurring national identity - Fatah, Prof.Dr.Media Ibrahim (Sulaimani Journal for Humanities, 2025)
The aim of the study is to demonstrate the effect of wearing the niqab on the blurring of national identity. The research community includes the total number of niqab wearers living in Erbil province. The research sample included 14 niqab wearers, 6 of them in Soran and 8 others in Erbil. This paper uses Manuel Castells' theory of the dual influence of religion on national identity in modern times. Research results have shown that the niqab as a distinctive symbol of Salafi Islam, which is the source of religious belief, blurs national identity and strengthens religious identity, especially in times of ideological conflict between them.
Keywords: Niqab; national identity; religious identity; religious ideology